SMART CITIES: AN EMPIRICAL STUDY OF DEFINITIONS - Batra, Ashish; Chhabra, Pankaj (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This research has been done alongside the objective of set up a clear definition of smart cities that could possibly utilized globally. Despite a lot of material on smart cities that are accessible, there is no defined, widely used set of terminology that would assist in accurately defining a "Smart City". Around 115 current smart cities definitions were analysed and examined by utilizing as a guideline the themes and attributes of smart cities. These definitions have been acquired from numerous sources such as user-centric definitions, company/corporate profiles, national and international organizations (United Nations, ITU, Indian Smart Cities Mission, etc.), government initiatives, academia & research communities, standards development organizations, and trade associations. A list of thirty important terms that need to be included in a standardized definition was determined, and important indicators and categories were also established. Finally, to conclude on the basis of the given analyses, a suggested definition for the “smart city” was given by the following: An innovative city is known as a "smart city" if it adopts ICTs (“information and communication technologies”) including innovative methods to enhance wellbeing, the effectiveness of urban services and environment, while simultaneously fulfilling the social, environmental, and economic requirements of both the present as well as the future generations. This derived definition is such a definition which can be generalized for any smart city with basic fundamentals terms mentioned in it and can be adopted widely throughout the world.